Perencanaan Welcome Area BBPLK Dengan Pendekatan Arsitektur Tematik - D.Debby Rifka; Faurantina Forlana Sigit; Rahmadhani Fitri; Novalinda (Universitas Medan Area, 2023)
BBPLK (Great Center for the Development of Job Training) is one of the job training centers in the city of Medan which is also known as the Indonesian Vocational Work Training (PLKI) under the coordination of the regional office of Indonesian workers in the province of North Sumatra. BBPLK itself has a park that has the potential to be used as an attractive plan, namely the welcome area where the site location is not well organized. The problem in this planning is how to plan the welcome area of the BBPLK park based on education and training landscapes with the Thematic Architecture approach. The design concept used is the concept of a clean cut thematic garden which is neatly based, well organized, and has three area divisions, namely the thematic garden area, the special training center area for landscapes, and the nursery placement area in the training park.